The Wingate anaerobic test: A comprehensive literature review and update on reference values in athletes - Christie, C. (All Graduate Plan B and other Reports. 1567, 2021)
The Wingate Anaerobic test (WAnT) was developed in the 1970s as a measurement of lower extremity anaerobic power (Ayalon, Inbar, Bar-Or, 1974) and has long been used as a measurement tool in athletes, who are often defined by numbers. While numbers are not able to entirely predict or evaluate athletic ability, they are often used as a tool to predict or rate athletes. The WAnT has long been a gold standard in evaluating lower extremity power, which is a highly valuable aspect of many sprint and power-driven sports (e.g., hockey, football, or track and field). The WAnT was originally developed and performed on a cycle ergometer that includes a subject pedaling for 30 seconds at maximal effort against a predetermined percentage of their body weight (BW), which has stood as the widely accepted method since development. There are multiple variables that can be adjusted at the investigators` discretion which may influence data output, including percentage of body weight (BW) as resistance, type of ergometer, time of testing in regard to participants` training macrocycle, duration of the WAnT, and inclusion of a familiarization session. Each of these variables can change the impact of reported data and reliability of a study compared to others. For instance, increasing or decreasing resistance may alter the ability of the participant to produce power efficiently, whereas shortening duration takes the lowest power values away from the calculation, increasing MP. These variables may be manipulated to achieve optimal performance outcomes.